Effect of Utilization of Native Language (Hausa) In Teaching Integrated Science Among Private Primary Schools Pupils; A Case Study of Gwadabawa Local Government Area, Sokoto State, Nigeria - ABUBAKAR, Abbas Hiliya (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Science is a key tool for national growth, security, and development of the entire world. The aim of science is only attained if there is good education. By emphasizing native language instruction, Nigeria can improve education quality, promote cultural preservation, and empower future generations. The objective of this paper was to determine the effect of using Hausa Language as medium of instruction among pupils of some private primary schools in Gwadabawa Local Government Area, Sokoto State, Nigeria. The study involved the use of an experimental design, whereby Hausa Language taught pupils are experimental group, and English taught pupils are control, consisting of 210 pupils selected by convenience sampling. The pupils were formatively assessed at the end of the study; and the results (p<0.05) indicate that pupils taught in Hausa Language score more mean marks (66.17+12.70) compared to their peers taught in English Language (with a new score of 46.20+10.11). Therefore, the results show the effectiveness of Hausa Language in affecting learning outcomes. Therefore, policy makers should look into the possibility of incorporating native languages like Hausa in instructions.